The Potential for Usury in The Implementation Of Tokopedia Card Transactions in E-Commerce Under Islamic Law - Ahmad Nafhani; Yunita Dewi Septiana; Irfan Harmain; Gusti Fadhil Fithrian Luthfan (Studia Economica : Jurnal Ekonomi Islam, 2026)
This study aims to analyze the implementation and legal status of transactions using the Tokopedia Card on e-commerce platforms from an Islamic law perspective. With the rapid development of financial technology, co-branded credit card products like the Tokopedia Card have become increasingly popular. The research method used is qualitative, employing a fiqh muamalah approach, which examines the operational mechanisms and contracts associated with the product. The analysis focuses on the main features of the Tokopedia Card as a conventional credit card issued by Bank BRI, such as the interest system, late payment fees, annual fees, and rewards programs. The analysis reveals that the interest on outstanding balances and late payment fees clearly fall under the category of Riba an-Nasi'ah, which is absolutely prohibited in Islam. Although features such as annual fees can be considered as ujrah (service fees) and rewards as permissible gifts, this does not negate the riba element that is at the core of conventional credit card contracts. The underlying agreement requires customers to agree to a riba-based system, which fundamentally contradicts the principles of sharia transactions. In conclusion, the implementation of transactions using the Tokopedia Card is inconsistent with Islamic law principles due to its prohibited riba elements. Muslim consumers are advised to use alternative payment methods free from riba elements, such as debit cards, electronic money, or Islamic credit cards